Keterampilan Mengajar Guru Sekolah Menengah di Kecamatan Pangenan, Cirebon - Taufik, Azin; Riyadi, Mohamad; Nurhayati, Nunu (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2024)
This service was motivated by the results of the Teacher Performance Assessment carried out at one of the schools assisted by the Madrasah Aliyah 3 Cirebon working group which stated that 60% of teachers did not have the competency skills that indicated they were professional teachers. The assessment team provided recommendations to improve teachers' teaching abilities so that the quality of learning could be better. One effort to improve teachers' teaching abilities can be done by providing training on eight basic teacher teaching abilities, training on student centered learning models and their application in preparing Learning Implementation Plans. In order to overcome this problem, it was implemented. on June 24 2024 training on basic teaching skills for teachers was carried out, on June 25 2024 training on student centered learning models was carried out, and on June 26 2024 feedback and evaluation of training results was carried out through the preparation of learning tool plans. The methods used in this training are lecture, question and answer and simulation methods, while the evaluation is carried out in two parts, namely evaluation during the training process and post-training evaluation.